Factors associated with the beginning of sexual life and adolescent pregnancy in Colombia. Cross-sectional study (2018)
Introduction: In Colombia, between 2008 and 2014, 23.4% of births were product of adolescent pregnancies, which have serious social, emotional and biological consequences for both the young mother and the baby. Materials and methods: Cross-sectional study with analytical component, with a sample of 13,313 women between 13 and 19 years of age who answered the National Survey of Demography and Health (ENDS) 2010. Bivariate analyzes and multinomial logistic regression analysis were carried out in order to identify individual, home-related, and sexual behavior factors associated with sexual debut and adolescent pregnancy among Colombian adolescents in 2010. Results: Multivariate analysis shown that being older, living together as a couple, having suffered parental violence, and having suffered sexual violence, were risk factors for initiation of sexual life and teenage pregnancy. School attendance was found to be a protective factor for both events. Poverty, overcrowding and lack of education were associated with teen pregnancy but not with sexual debut. Conclusions: There are multiple factors associated with early sexual debut and adolescent pregnancy which are susceptible to intervention. This study presents key factors to generate prevention programs for these situations. © 2018 Sociedad Chilena de Obstetricia y Ginecologia. All rights reserved.